FORESTS AND FOREST RESERVES AS SECURITY THREATS IN NORTHERN NIGERIA - Ladan B.A, Suleiman Iguda (European Scientific Journal, ESJ, 2014)
Forests are important plant communities that consist of trees and other woody vegetation that performs life supporting functions on earth. This paper attempts to examine forests and forest reserves as security threats in the northern region of Nigeria, Africa’s most populous nation. The study is both empirical and theoretical in nature as both primary and secondary sources of data were collected, edited and analyzed for the research. The results identified the reasons why forests and forest reserves can be security threats as indicated using examples in countries from different parts of the world such as Colombia, Kenya, Democratic Republic of Congo and India. The results further identified eight forests and forest reserves in the region using their location, specie composition and present status. The security threats they posed were examined which include bases, hideouts and camping sites for insurgents, highway armed robbers, thieves and other criminals. The study proposed the way out of the present insecure situation through launching attack to dislodge the insurgent, protection of forests and forest reserves, reforestation of degraded sections among others. These forests and forest reserves need to be properly harnessed and developed into recreational parks and tourist centers that will yield the much needed revenue to the governments of northern Nigeria.